Problems and solutions in the use of terms in Russian - Umarbekova Gulnora Anvarbekovna (Genius Journals, 2022)
Technical necessity and need lead to the development of science. The development of branches of science, the emergence of new branches and directions of science, of course, will lead to the improvement of the existing system of terms, the emergence of new terms. This, in turn, leads to the emergence of new problems, issues and tasks in linguistics. At the same time, the issue of the integrity of language and thinking is gaining new qualitative features as a result of the development of terminological vocabulary.
Keywords: Terminology; Linguistics; Problem; Communication